Protective Treatment of Fire Pipe Hose Against Microbial Degradation-Part II - Dayal, H. M.; Nigam, S. S.; Agarwal, P. N. (Defence Science Journal, 2014)
Fire pipe hoses are liable to suffer heavy microbial damage under tropical conditions. Treatment with Mystox LPL 100% at 5% concentration has been found to confer effective protection.